PENGARUH PEMBERIAN PROBIOTIK DARI MIKROBA LOKAL TERHADAP GAMBARAN DARAH AYAM PETELUR - Lutfiana, Konita; Kurtini, Tintin; Hartono, Madi (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
The purpose of this research was 1) investigated the effect of additional probiotic from local microbial to blood description of layer, especially erythrocytes and hemoglobin; 2) investigated the level of optimalitation additional probiotic from local microbial of layer. The research was conducted on 20th of December 2014 until 19th of January 2015 in Varia Agung Jaya village, Seputih Mataram subdistrict, Lampung Tengah. The fabrication of probiotic from local mikrobial at 8th until 19th December 2014 in the Laboratory of Molecular Biology, Lampung University. This experiment arranged a completely randomized design (CRD) with 4 probiotic levels of local microbes (0%, 1%, 2%, and 3%) and 5 replications. The data obtained were analyzed using Analysis of Variance at 1% and continued with Polynom Orthogonal test at 1%. The result of this research showed that the additional of probiotic from local microbial (0%, 1%, 2%, and 3%) was not significant effect (P>0,05) to the number of erythrocytes of layer, but highly significant effect (P <0,01) to the number of hemoglobin. Probiotic levels of local microbial (0%, 1%, 2%, and 3%) can increase the number of hemoglobin with regression equality (Ŷ = 6,68 + 0,48X). (Keywords: Layer, Probiotics from local microbial, The number of erythrocytes and Hemoglobin)